Rare bird documentation form for Peregrine Falcon at Grammer Grove County Wildlife Area, 1986 - Proescholdt, Market al (1986)
Rare bird documentation form for two Peregrine Falcons at Grammer Grove County Wildlife Area in Marshall County, IA on September 20, 1986. Epson - sheet feed